Prevalensi dan Kepadatan Mikrofilaria pada Desa Non-Endemis Pasca Pengobatan Massal Tahun Keempat di Kabupaten Tanah Bumbu - Juhairiyah Juhairiyah; Dwi Candra Arianti; Erli Hariyati; Deni Fakhrizal; Paisal Paisal (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
Research conducted at several places in Indonesia stated that mass treatment can reduce the level of endemicity of filariasis. Tanah Bumbu Regency has conducted mass treatment for 4 years in a row with the results of MF rate in sentinel villages decreased, However, there are still filariasis sufferers who do not take the drug so that research is needed in other spot villages in Tanah Bumbu Regency to determine the success of POPM. This study is an observational study with a cross-sectional design that was conducted at the Satiung/spot village. The sampling technique is based on treatment evaluation rules. Respondents who are willing to have their blood drawn will be examined for the presence of microfilaria using microscopic methods and polymerase chain reaction (PCR) and will be asked a questionnaire about the characteristics and compliance of respondents to POPM. Data were analyzed descriptively and presented in tables and graphs. Total respondents 318 with the characteristics are mostly housewives at a productive age range, the percentage of respondents taking drugs is quite high at 86.16%, but still found the respondents did not take a medicine that can cause further infection source. PCR examination found 2 positive samples of Brugia malayi microfilaria from 318 samples (Mf rate = 0.63%), the average density of 116.9 in 1 ml of blood in one patient did not routinely take medicine every year. Efforts should be made to increase public compliance with POPM by conducting counseling and supervision on taking drugs.